“Seeker” Platform LMS Pengembangan dan Penyediaan Tenaga Kerja Kompeten - Hasirun; Herjuna Ardi Prakosa; Joda Rachindratama; Putra Maulana Zahbika; Zanuar Rifai; Husni Faqih; Fiby Nur Afiana (POLITEKNIK NEGERI JAKARTA, 2025)
The Industrial Revolution 4.0 is estimated to eliminate 23 million jobs but create 46 million new types of jobs based on technology such as IoT, AI, and Big Data. This change demands the readiness of human resources, including in the MSME sector, as well as increased digital competency. Many companies now require skills certification in addition to formal diplomas. LMS (Learning Management Systems) are present as digital learning solutions that manage materials, assignments, and online learning interactions. However, most LMSs still focus on formal education, not on developing skills for high school/vocational school or university graduates. The aim of this research is to combine elements of LMS and job seekers in an effort to strengthen the advantages of future generations through competitive qualifications, skills, and technology in the industry. This platform allows collaboration with educational institutions, industry, and MSMEs to build a strong cooperative ecosystem in the socio-environmental field. Using the Prototype method as a software development method to support the success of the research. The LMS